2010
DOI: 10.1057/pol.2009.21
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Torture

Abstract: Despite being the subject of much recent scholarly work, torture remains an ambiguous concept. As recent legal arguments have made clear, such vagueness has important and immediate political consequences. This article makes a number of contributions towards resolving this ambiguity. First, it argues that the distinction between physical and psychological abuse is unwarranted. Second, it puts forward a logical basis for the distinction between torture and legally permissible punishments like incarceration. Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…90 Kenny, who ten years later argues for a "comparative method" in Indian place-name analysis, believes that Indian place-names deserve separate consideration from those of à à à European origin: "Such names, to begin with, are from intricate American languages; when they are cast into the maelstrom of our English and European names they are out of place and may seem less important and interesting than they are." 91 Thus from the mid-twentieth century the study of American Indian place-names becomes much more scholarly and linguistically oriented, with or without the involvement of actual Indians.…”
Section: Dying Indians Internal and Eternalmentioning
confidence: 99%
“…90 Kenny, who ten years later argues for a "comparative method" in Indian place-name analysis, believes that Indian place-names deserve separate consideration from those of à à à European origin: "Such names, to begin with, are from intricate American languages; when they are cast into the maelstrom of our English and European names they are out of place and may seem less important and interesting than they are." 91 Thus from the mid-twentieth century the study of American Indian place-names becomes much more scholarly and linguistically oriented, with or without the involvement of actual Indians.…”
Section: Dying Indians Internal and Eternalmentioning
confidence: 99%
“…Others reject the “public official” condition as too restrictive. For instance, Kenny (2010) instead emphasizes the “instrumentality” of torture: suffering is intentionally caused in order to elicit a behavioral response, in a situation where the torturer has control over the victim 2 . The two psychiatric diagnoses most often associated with the effects of torture are major depression and PTSD, which are difficult to tease apart when diagnosed together ( Istanbul Protocol, 1999 , p. 45).…”
Section: Torture and Traumamentioning
confidence: 99%
“…First, political theory has sought to illuminate the political world, not just talk about texts, and offers new perspectives on current issues that empirically oriented scholars may neglect. Theory has concerned itself with such timely matters as the expansion of executive power under emergency circumstances, 21 the use of torture, 22 the balance between the need of the state for secrecy and individual civil liberties, 23 religious education in a democracy, 24 the Christian Right in the United States, 25 healing the emotional scars caused by political murders, 26 and hypocrisy among political leaders. 27 Second, even when discussing texts, theorists have demonstrated that interpretation provides a vehicle for gaining new purchase on political issues.…”
Section: The State Of the Discipline Polity Versionmentioning
confidence: 99%